Winning the Service Game - Benjamin Schneider; David Earl Bowen (Boston, MA Harvard Business School Press, 1995)
This text offers guidelines on what it takes to deliver outstanding service. It presents over 50 explicit rules for delivery service quality and it argues that in order to gain competitive advantage in customer service, companies must focus on retaining customers. The book's findings are based on dozens of company examples and a decade of research.
Age Group: Adult
Includes bibliographical references (p. 261-283) and index.
Keywords: Customer services; Management; Training of employees; Incentives in industry; Customer Services -- Management; Employees -- Training Of